THE POETRY OF ARTIST VOLODYMYR HAVRYLIUK (based on the collection «Shadow and traveller») - Mocherniuk, N. D. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is a part of research of Ukrainian artist and poet Volodymyr Havryliuk’s creative work. The peculiarities of the poetics of collection «Shadow and traveller» are examined. The connection of poetry and painting in artist’s biography is underlined. The incorporations of art themes and terminology, ekphrasis, specifics of landscapes in Havryliuk’s poetry are defined.